Revision of the Agrilus quadripunctatus species-group (Coleoptera: Buprestidae: Agrilini) with description of four new species - Jendek, Eduard (Zootaxa, 2018)
The newly defined Agrilus quadripunctatus species-group comprising nine species from Indo-Malay and Australasian regions is revised. A key to species is provided and complemented with illustrations of habitus. The following four new species are described: Agrilus calabai sp. nov.; A. jaechi sp. nov.; A. luzonicola sp. nov.; A. salakot sp. nov.